The Role of The Ethnic Borneo Studio as An Empowered Community in The Development of Traditional Arts in The City of Samarinda: Peranan Sanggar Borneo Etnika Sebagai Komunitas Berdaya Dalam Perkembangan Kesenian Tradisional Di Kota Samarinda - Maurani, Sonia Adinda Septi; Sukapti, Sukapti; Nasir, Badruddin (Progress In Social Development, 2021)
ABSTRACT: The Borneo Etnika Studio is one of the studios in Samarinda City that was founded in 2008 and turned into a community in 2013 with a wider focus on art. The training and coaching activities include basic theory in dancing and playing traditional musical instruments which consist of three realms of artistic culture which include the palace, the coast and the hinterland. The Borneo Etnika Studio opened the activity in general to the wider community, then the studio as a supporting element in developing traditional arts also played its role in creating new works by participating in various kinds of performances and competitions as well as collaborating with the local government, one of which was UPTD Taman Budaya which is a facilitator in providing a place for the activities carried out by the Borneo Ethnic Studio. ABSTRAK: Sanggar Borneo Etnika merupakan salah satu sanggar di Kota Samarinda yang berdiri sejak tahun 2008 dan berubah menjadi komunitas pada tahun 2013 dengan fokus seni yang lebih luas. Kegiatan pelatihan dan pembinaan didalamnya meliputi teori dasar dalam menari dan memainkan alat musik tradisional yang terdiri dari tiga ranah budaya kesenian yang meliputi keraton, pesisir dan pedalaman. Sanggar Borneo Etnika membuka kegiatan tersebut secara umum untuk masyarakat luas, kemudian sanggar sebagai unsur pendukung dalam mengembangkan kesenian tradisional juga menjalankan peranannya dalam menciptakan karya-karya terbaru dengan mengikuti berbagai macam pementasan dan perlombaan serta menjalin kerjasama dengan pemerintah setempat salah satunya UPTD Taman Budaya yang merupakan fasilitator dalam menyediakan tempat untuk kegiatan yang dilaksanakan Sanggar Borneo Etnika.